Pondok Pesantren Lubuk Sikaping Dengan Pendekatan Arsitektur Organik - Lusi Novita; Pedia Aldy; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The design of Islamic Boarding School is meant to fulfill Islamic education needs. This design aims to accommodate public education and Islamic facilities which there are education levels of Mts and MA. This Islamic Boarding School facility be able add a place of Islamic education in Lubuk Sikaping. This design uses the approach of Organic Architecture. The approach is applied partly or overall on buildings. Organic Architecture paying attention to the environment collaboration with the site. This approach is accordance with Islamic Boarding School which is Islamic Education, where Islam teaches about nature and environment.The same is true in education that learns from nature and environment. Root is the basic concept of design that can connect education, Islam and organic. The concept obtained by the site is in a relatively contoured area, which has the same characteristic of the root such as free, besides it in the site there are also many trees. Roots is the most prominent thing on the site. The form and some of the characteristics of the root are the inspiration in designing a boarding school. The elongated characteristic of the root is the inspiration for building masses which is analogous to rectangles, where of the nine building masses there is no similar shape. The nature of the root that rests on one point is the inspiration for circulation where the mosque becomes the focal point of all activities. Key word: Key word: Education, Islamic Boarding School, Islam, Organic Architecture